Pretreatment Of Dewatered Sludge Formicrobial Fuel Cell Application - Rusdi, Nur Fatin Syahira (Universiti Sains Malaysia, 2017)
In this study, influence of different method of pretreatment of dewatered sludge for microbial fuel cell (MFC) performance was investigated. This study investigated the effects of different methods (alkaline and acidic pretreatment) with varying pH (9, 8, 7, 6, 5, and 4) on 24 hours of pretreatment. First, effect of sludge pretreatment was analysed by Chemical Oxygen Demand (COD) solubilisation and Volatile Organic Acids (VOA). After 24 hours of pretreatment, COD solubilisation and VOA was higher for alkaline pretreatment and lower for acidic pretreatment. Second, with 7 days of operation at batch mode, single chamber microbial fuel cell (SCMFC) was run with pretreated sludge (external resistance - 1000Ω). Alkaline pretreatment showed a decrease of Soluble Chemical Oxygen Demand (SCOD) up to 46% meanwhile the value for acidic pretreatment was 23%. From experimental results, it was indicated that the maximum voltage generation with open circuit voltage (OCV) of 691mV at pH 6 was generated in 7 days. The conductivity of the pretreated sludge for both methods decreased during the 7 days operation. Thus, these results showed that using pretreated sludge as the substrates in MFC could achieve both sludge reduction and electricity generation, and proper pretreatment of sludge could improve the overall process.